Die gedaante van die historiese feit op film: ‘n Sintese tussen waarheid en verdigsel (Historia, 2021)
The film making industry has always had a passion for glitter. Consequently it would seldom let truth stand in the way of a good story. In the article there is an explanation of how history has been coloured in by the film industry. A variety of themes, ranging from South African films, films dealing with South Africa, war, peace, historical figures, politics and social trends are discussed. By means of references to films, from the beginning of the twentieth century up to the present, there are indications that a wealth of historical information is hidden in the medium of film. The conclusion is made that nowadays there are attempts at recording history before it even happened. By recording the event of historical significance the film makers in fact buy the rights to that story. The question however persists: How much is true and how much is false?
Keywords: Historiography; History; Historical films; Films; Film industry